Low‐Voltage, High‐Performance, Indium‐Tin‐Zinc‐Oxide Thin‐Film Transistors Based on Dual‐Channel and Anodic‐Oxide. (29th December 2022) - Jin, Jidong; Lin, Xiaoyu; Zhang, Jiawei; Lee, Jeongho; Xiao, Zhenyuan; Lee, Soobin; Kim, Jaekyun
Abstract: Oxide semiconductor thin‐film transistors (TFTs) with low‐voltage operation, excellent device performance, and bias stability are highly desirable for portable and wearable electronics. Here, the development of low‐voltage indium‐tin‐zinc‐oxide (ITZO) TFTs with excellent device performance and bias stability based on a dual‐channel layer and an anodic‐oxide dielectric layer are reported. An ultra‐thin anodic Alx Oy film as a gate dielectric layer is prepared using an anodization process. The dual‐channel layer consists of an oxygen‐uncompensated channel layer and an oxygen‐compensated capping layer. It is confirmed that the dual‐channel structure is effective for enhancing device performance and bias stability in comparison with the single‐channel structure. As a result, the dual‐channel ITZO TFT gated with anodic Alx Oy exhibits an effective saturation mobility of 12.56 cm 2 Vs −1, a threshold voltage of 0.28 V, a subthreshold swing of 76 mV dec −1, a low‐voltage operation of 1 V, and good operational stability (threshold voltage shift (Δ V TH ) < −0.03 V under a negative gate bias stress and Δ V TH < 0.15 under positive gate bias stress of 3600 s). The work shows that the ITZO TFTs, based on a dual‐channel layer and an anodic‐oxide gate dielectric layer, have great potential for low‐power, portable, and wearable electronics. Abstract : Low‐voltage operation of indium‐tin‐zinc‐oxide (ITZO) thin‐film transistors (TFTs) with excellent device performance and bias stability based on a dual‐channel layer and an anodic‐oxide dielectric layer are achieved. The operating voltage of the ITZO TFTs is as low as 1 V due to the high capacitance of the ultra‐thin anodic Alx Oy gate dielectric layer formed through anodization.